Problems of forecasting in designing the development of oil, gas and gas condensate fields - Abdirazakov Akmal Ibrahimovich; Mavlanov Zafar Alanazarovich (Genius Journals, 2024)
This article provides analytical information on the importance of not only collecting data in the oil and gas industry, but also ensuring the accuracy and correlation of geological data, as well as the identity of their change over time when forming them as a specific database and creating a development model.
Keywords: information; object; abstraction; structure